2019
DOI: 10.12669/pjms.35.4.534
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between monocyte to high-density lipoprotein cholesterol ratio and diabetic nephropathy

Abstract: Objective: This study aims to investigate the relationship of monocyte to high-density lipoprotein cholesterol ratio (MHR) with diabetes mellitus (DM) and diabetic nephropathy. Methods: This study included 262 Type-2 diabetes mellitus patients, of which 60 had diabetic nephropathy and 202 did not have diabetic nephropathy who presented to the internal diseases polyclinic at Firat University Medical Faculty Hospital between May 2018 and October 2018 and 50 healthy control subjects. A retrospective scan of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
1
24
0
4
Order By: Relevance
“…Combining two indicators of opposite changes, MHR is a valuable marker in systemic inflammatory diseases. It is being increasingly recognized as a novel clinically relevant biomarker of pathological inflammation and a new predictor and prognostic factor in cardiovascular disease, cerebrovascular disease, peripheral artery disease, metabolic syndrome, diabetic nephropathy, and multiple sclerosis 23‐31 . Nonetheless rarely has MHR been studied in thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Combining two indicators of opposite changes, MHR is a valuable marker in systemic inflammatory diseases. It is being increasingly recognized as a novel clinically relevant biomarker of pathological inflammation and a new predictor and prognostic factor in cardiovascular disease, cerebrovascular disease, peripheral artery disease, metabolic syndrome, diabetic nephropathy, and multiple sclerosis 23‐31 . Nonetheless rarely has MHR been studied in thyroid disease.…”
Section: Discussionmentioning
confidence: 99%
“…MHR increase parallel to decreased eGFR has been shown. 20 Karatas et al reported that MHR was positively correlated to the urinary albumin / creatinine ratio, independent of all other variables. 21 Similarly, Kahraman et al reported that MHR was positively correlated to 24-hour urinary albumin excretion and negatively correlated to GFR.…”
Section: Discussionmentioning
confidence: 97%
“…21 Other studies have shown that Rhodiola rosea can increase high density lipoprotein, reduce low density lipoprotein, and regulate the effect of blood lipids. 15 - 17 …”
Section: Discussionmentioning
confidence: 99%